2013
DOI: 10.14233/ajchem.2013.14173
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Humic Acid from Aqueous Solution on Single-Walled Carbon Nanotubes

Abstract: Contamination of surface water and necessity of accessing new water resources is one of the biggest problems of most developing countries. This has allocated most national and international plans to itself. Most water resources throughout the world especially surface and groundwater have huge amounts of natural organic matters (NOMs). Natural organic matters are a product of degradation of aqueous plants and algae available in surface water resources 1. These matters are a complex and heterogeneous mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Their study results showed that data followed pseudo-second order reaction. Their study results correspond with present study results [25]. Ai and his assistants studied about removal of methylene blue from aqueous solution with magnetite loaded multi-wall carbon nanotube.…”
Section: Discussionsupporting
confidence: 90%
“…Their study results showed that data followed pseudo-second order reaction. Their study results correspond with present study results [25]. Ai and his assistants studied about removal of methylene blue from aqueous solution with magnetite loaded multi-wall carbon nanotube.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to ferromagnetic properties, the room temperature specific magnetization (M) versus applied magnetic field (H) curve measurement of the AC/CFO indicates that the values of coercive force [38], saturation magnetization and remnant magnetization are 433.02 Oe, 22.03 emu/g and 7.16 emu/g, respectively; a similar result was reported earlier by Xu et al [39].…”
Section: Magnetic Properties Of Ac/cfosupporting
confidence: 85%
“…The solution was then poured into a beaker and agitated for three hours. The solution obtained after three hours of agitation was purified humic acid with concentration 1 g/L, which was stored at 4 °C [1,2,[6], [7], [8], [9], [10]].…”
Section: Description Of Protocolmentioning
confidence: 99%